A Study on the Correlation between Motivation and Students’ Speaking Performance at an Indonesian Vocational High school Context - Ratnawati Ratnawati; Sumirna Sumirna; Hikma Nurul Isma (Universitas Negeri Makassar, 2019)
This study aims to find out vocational high school students’ speaking performance in correlation with their motivation to learning English. This study employs a quantitative research method using questionnaire to gather the data. The whole population in this study was the first grade of SMK Negeri 6 Makassar which consists of three classes numbering 86 students. The samples were students from class b which consists of 25 students. The sample was taken by using purposive sampling technique. This study was conducted by distributing questionnaires to students who were respondents and test, after which they were input and analyzed through the SPSS program. The findings revealed that the correlation between motivation and speaking performance for vocational high school students indicated that it was strong enough or categorized as medium correlation. Furthermore, the findings showed that the motivated students usually feel more comfortable in their learning providing the students to speak up confidently wherever they are even although English is considered as a foreign language.